2008
DOI: 10.1007/s10867-008-9068-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonlinear Delayed Feedback on Synchronized Oscillators

Abstract: We show that synchronization processes can effectively be controlled with nonlinear delayed feedback. We demonstrate that nonlinear delayed feedback can have a twofold impact on the collective dynamics of large ensembles of coupled oscillators: synchronizing and, mostly, desynchronizing effects. By means of a model equation for the mean field, we explore the existence and stability of the feedback-induced desynchronized states, their multistability and dynamical properties. We propose nonlinear delayed feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Moreover, the desynchronization regions occupy larger domains of the parameter space and increase in size for larger values of the stimulation intensity K . The favorable desynchronizing effect of NDF at large stimulation intensities has been revealed for several other models and stimulation setups 50, 54, 56, 76, 78 . We therefore investigate the behavior of the order parameter of the stimulated STN neurons while the parameter of the stimulation intensity K increases.
Figure 7Impact of the pulsatile NDF stimulation (7) on the neuronal ensemble (1)-(3).
…”
Section: Resultsmentioning
confidence: 80%
“…Moreover, the desynchronization regions occupy larger domains of the parameter space and increase in size for larger values of the stimulation intensity K . The favorable desynchronizing effect of NDF at large stimulation intensities has been revealed for several other models and stimulation setups 50, 54, 56, 76, 78 . We therefore investigate the behavior of the order parameter of the stimulated STN neurons while the parameter of the stimulation intensity K increases.
Figure 7Impact of the pulsatile NDF stimulation (7) on the neuronal ensemble (1)-(3).
…”
Section: Resultsmentioning
confidence: 80%
“…Clinical studies have reported a reduction in the level of beta-band activity following the application of DBS [8], [4], leading to the LFP's being suggested as a biomarker for use in the design of closed-loop DBS [9]. Whilst computational investigations of "mild" stimulation methods, such as coordinated reset and mean field feedback, suggest a return to physiological network activity [12], [13], [14], closed-loop high frequency DBS relies on the same underlying mechanisms of action as openloop DBS. It is likely that closed-loop high frequency DBS would be more immediately suitable for implementation than alternative closed-loop methods, due to the similarity of the signal generation circuitry to current open-loop technology.…”
Section: Discussionmentioning
confidence: 99%
“…The first uses high-frequency DBS waveforms as currently used in open-loop configuration, but applies closed-loop control to vary the stimulation parameters [10]. The second, termed "mild stimulation", attempts to desynchronise pathological oscillatory networks in an on-demand fashion [11], [12], [13], [14]. At present, the only implanted stimulation hardware for closed-loop DBS that has been proposed for clinical use is designed to deliver high-frequency DBS [15].…”
Section: Introductionmentioning
confidence: 99%
“…Till now, several methods such as desynchronization with pulsatile stimulation protocols (Tass 1999(Tass , 2001a(Tass ,b, 2002(Tass , 2003, time delayed feedback (Rosenblum and Pikovsky 2004a;Popovych et al 2005), and proportional-integro-differential feedback (Pyragas et al 2007) have been presented in theoretical and numerical studies. For its effectiveness and robustness, time delayed feedback for desynchronization in ensembles of globally coupled oscillators has been extensively studied (Rosenblum and Pikovsky 2004a,b;Popovych et al 2005Popovych et al , 2006Popovych et al , 2008Hauptmann et al 2005;Rosenblum et al 2006). However, it may bring undesirable instability and requires careful parameter tuning.…”
Section: Introductionmentioning
confidence: 99%